SYSTEMATIC LITERATURE REVIEW: CHALLENGES AND SOLUTIONS ON AGILE PROJECT MANAGEMENT IN PUBLIC SECTOR - Mekkawati, Handini; Raharjo, Teguh; Yuniarti, Rina (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2024)
The public sector is transforming by adopting an agile approach to overcome bureaucratic rigidity and lagging the private sector. The aim is to overcome the limitations of traditional approaches by encouraging flexibility in planning, operations, and service delivery. In the face of diverse, agile characteristics, further research is required on the challenges and best practices other public sector organizations can adopt. This research identifies key challenges in agile implementation within the PMBOK 7th edition project performance domains with the most issues: Development Approach and Life Cycle and Project Work Domain. Using a systematic literature review (SLR), 35 of 680 reviewed papers were selected as references. The biggest challenges were in the Project Work Domain, dominated by the context of monitoring new work and changes, project processes, and procurement processes. Best practices were identified to address these challenges and guide other public sectors in supporting more flexible and responsive public service delivery.